From Research to Clinical Settings: Validation of the Affect in Play Scale – Preschool Brief Version in a Sample of Preschool and School Aged Italian Children - Di Riso, Daniela; Salcuni, Silvia; Lis, Adriana; Delvecchio, Elisa (Frontiers in Psychology, 2017)
Affect in Play Scale-Preschool (APS-P) is one of the few standardized tools to measure pretend play. APS-P is an effective measure of symbolic play, able to detect both cognitive and affective dimensions which classically designated play in children, but often are evaluated separately and are scarcely integrated. The scale uses 5 minutes standardized play task with a set of toys. Recently the scale was extended from 6 to 10 years old and validated in Italy preschool and school-aged children. Some of the main limitations of this measure are that it requires videotaping, verbatim transcripts, and an extensive scoring training, which could compromise its clinical utility. For these reasons, a Brief version of the measure was developed by the original authors. This paper will focus on an APS-P Brief Version and its Extended Version through ages (6 to 10 years), which consists “in vivo” coding. This study aimed to evaluate construct and external validity of this APS-P Brief Version and its Extended Version in a sample of 538 Italian children aged 4-to-10 years. Confirmatory Factor Analysis yielded a two correlated factor structure including an affective and a cognitive factor. APS-P-BR and its Extended Version factor scores strongly related to APS-P Extended Version factor scores. Significant relationships were found with a divergent thinking task. Results suggest that the APS-P-BR and its Extended Version is an encouraging brief measure assessing pretend play using toys. It would easily substitute the APS-P and its Extended Version in clinical and research settings, reducing time and difficulties in scoring procedures and maintaining the same strengths.